KAJIAN UMUR BIBIT BATANG BAWAH NANGKA DAN TAKARAN PUPUK PELENGKAP BENIH NUTRIFARM-SD TERHADAP KEBERHASILAN PERTAUTAN SAMBUNG PUCUK - Yohanis Tambing; Syamsuddin Laude (Universitas Tadulako, 2009)
The research aimed at determining the age of nangka rootstock and the level of Nutrifarm-SD fertilizer on the successful knitting of grafting. The research was arranged in a Randomized Block design in a factorial experiment in which grouping was based on the rootstock length. Two factors applied included the age of the rootstock: 1 month after sowing (BST), 2 months after sowing, and 3 months after sowing and the levels of Nutrifarm-SD: control, 5 g seed kg-1, 10 g seed kg-1, and 15 g seed kg-1. Grafting using younger rootstock (1 month after planting) resulted in the largest number of successful bonding. Either the single effect of Nutrifarm-SD fertilizer or combined effect with the age of the rootstock was insignificance on all parameters observed.